A genus and three new species for Spain with other additional interesting lepidopterology information for the Spanish fauna. Description of the females of Agnoea revillai Gastón & Vives, 2020 and creation of a new genus Paramegacraspedus Gastón & Vives, gen. n. (Insecta: Lepidoptera) - J. Gastón; A. Vives Moreno (SHILAP, 2021)
A new genus Paramegacraspedus Gastón & Vives, gen. n. Gelechiidae) is described. For the first time for the fauna of Spain: Bucculatrix ratisbonensis (Stainton, 1861) Bucculatricidae), Coleophora sattleri Baldizzone, 1995 (Coleophoridae) y Anacampsis trifoliella (Constant, 1890) (Gelechiidae) are mentioned. The female of Agnoea revillai Gastón & Vives, 2020 (Lypusidae) is described. The presence of Megacraspedus dolosellus (Zeller 1839) is confirmed for Spain.